2020
DOI: 10.1186/s12864-020-06843-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual indexed library design enables compatibility of in-Drop single-cell RNA-sequencing with exAMP chemistry sequencing platforms

Abstract: Background The increasing demand of single-cell RNA-sequencing (scRNA-seq) experiments, such as the number of experiments and cells queried per experiment, necessitates higher sequencing depth coupled to high data quality. New high-throughput sequencers, such as the Illumina NovaSeq 6000, enables this demand to be filled in a cost-effective manner. However, current scRNA-seq library designs present compatibility challenges with newer sequencing technologies, such as index-hopping, and their ability to generate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…, 2011 ), our analysis of recently generated single-cell RNAseq (scRNAseq) data from the intestinal tract ( Banerjee et al. , 2020 ; Southard-Smith et al. , 2020 ) revealed that NM2C is preferentially expressed in mature villus enterocytes relative to NM2A or NM2B, the latter of which was barely detectable (Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…, 2011 ), our analysis of recently generated single-cell RNAseq (scRNAseq) data from the intestinal tract ( Banerjee et al. , 2020 ; Southard-Smith et al. , 2020 ) revealed that NM2C is preferentially expressed in mature villus enterocytes relative to NM2A or NM2B, the latter of which was barely detectable (Supplemental Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogel beads dissolve in the droplets, releasing the oligonucleotides to hybridize the mRNAs, and the reverse transcription reactions are carried out within the drops. However, the major drawback of inDrop is the extremely low cell capture efficiency, which could detect only 20–50 copies of transcripts per cell [ 118 ]. This technology enables the scRNA-seq of large numbers of cells, which allows the identification of very rare cell types from heterogeneous populations.…”
Section: Comparative Analysis Of High-throughput Scrna-seq Methodsmentioning
confidence: 99%
“…However, Drop-seq requires custom, “lab-made” microfluidics devices which requires technical engineering expertise [ 37 ]. InDrop has a commercially available platform, but the cell and transcript capture efficiency is low [ 38 ]. These microfluidics scRNA-seq approaches are beneficial because the RNA extraction and library preparation can occur within the microfluidic chip; however, these approaches can be problematic because they require either technical expertise or they are not sensitive to the distribution of transcripts and cells in a sample.…”
Section: Considerations When Planning a Scseq Study In Non-model Orga...mentioning
confidence: 99%